PARADIGMA BADAN LAYANAN UMUM SEKOLAH TINGGI PENERBANGAN INDONESIA ( PK BLU STPI ) - Solihin; Bunyana Sopari; Saptono (Langit Biru: Jurnal Ilmiah Aviasi, 2017)
Paradigm Public Service Agency Indonesian Civil AviationTrainning Centre is thought breakthrough made to meet the demanding needs of human resources in the field of aviation covering all aspects of aviation, the Financial Administration of the Public Service (PK BLU) is not easy back your hand in organizing the governance changes such financial (PK BLU), in which the Indonesian Civil Aviation Trainning Centre is a college that has the duty and function of educating the nation's best students of the Indonesian Civil Aviation Trainning Centre to become human resources and skilled experts in the field of aviation, which is recognized both nationally and internationally. Financial management education and training activities carried out initially using the system's bureaucracy into a pattern Entreupreneur. For all the education providers to change the way he thought it Entreupreneur.